Promotion of Modern Tourism in Lampung Province with the Scaffolded Reading Method in the New Normal Era - Al Rajafi, Gali; Wahyuingsih, Yulia (ELT-Lectura, 2022)
In the midst of the COVID-19 outbreak, learning activities became online, resulting in a change in the teaching system. In English, there are several skills that are usually done face-to-face, but due to the covid-19 outbreak, all learning is done online. Ideally, reading skills should be done face-to-face. Of course this is a concern for lecturers in determining learning methods, so that online-based learning outcomes can represent offline learning in a balanced way. In addition, students can also be well facilitated during the learning process like face-to-face learning. The second concern arose because researchers saw a fairly large impact due to the Covid-19 outbreak, especially in the field of tourism. Lampung Province has a lot of contemporary tourism potential that can be a regional and national asset. Since the outbreak of Covid-19, tourism potential has weakened and is getting worse. The purpose of this study is to improve reading skills, increase understanding of the current tourism potential of Lampung Province, and promote the current tourism potential of Lampung Province in the English Club community of Universitas Muhammadiyah Lampung in the new normal era. This study uses a quantitative approach. The method used is Quasi Experimental design. The steps taken include: 1) giving a pre-test several times; 2) provide treatment; 3) give a pot-test several times.